Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Gulf of Mexico)--Sand seatrout and silver seatrout - Sutter, Frederick C.; McIlwain, Thomas D. (Washington U.S. Department of the Interior, 1987)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.72)
Keywords: Invertebrates; Fishes; History; Sand seatrout and silver seatrout--Gulf of Mexico